Murder at the spelling bee - Hollis, Lee (Hollis, Lee. Maya & Sandra mysteries., 2024)
Twelve-year-old Rocco Fanelli is a spelling bee champ in the making. He’s the odds-on favorite to win the local middle-school bee and go on to the regionals, the state, and ultimately the nationals. Which is why someone is trying to intimidate him to drop out with a threatening note in his locker. Rocco’s concerned parents hire Maya and Sandra to uncover the culprit and ensure their son’s safety.But the competition turns killer when a high school teacher who’s running the bee, clearly favoring certain students, is found dead in the school supply closet. Sandra had already confronted Ellie Lambert over unfairly grading her son Ryan—which now makes her a suspect.She’s not the only one who tangled with the teacher, however, and with suspects ranging from helicopter parents to the school custodian, Maya and Sandra will need to put their heads together to spell out who had the motive and opportunity to silence Ellie Lambert . . .